2018
DOI: 10.1159/000489073
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Pluripotent Stem Cell-Derived Cardiomyocyte Toxicity by Supernatant of Long Term-Stored Red Blood Cells in Vitro

Abstract: Background/Aims: Preserved red blood cells (RBCs) in vitro undergo a series of morphological, functional and metabolic changes during storage. RBC metabolites accumulate over time during storage, the toxicity of the supernatants of RBCs (SSRBCs) on tissue cells is largely unknown. Here, we aimed to study cardiomyocyte toxicity by supernatant of long term-stored RBCs in vitro and to discover elements involved in the mechanism. Methods: Using human-induced pluripotent stem cell-derived cardiomyocytes (hiPS-CMs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(34 reference statements)
1
0
0
Order By: Relevance
“… 25 The Na + levels in both groups increased, and the short-term group had higher levels than the long-term group, which may be related to hemolysis of stored SRBC. 26 In addition, our study also showed that the incidence of adverse reactions in the short-term group (4.00%) was lower than that in the long-term group (18.00%), which was similar with the study results of Fan et al 27 and Robinson et al 28 …”
Section: Discussionsupporting
confidence: 91%
“… 25 The Na + levels in both groups increased, and the short-term group had higher levels than the long-term group, which may be related to hemolysis of stored SRBC. 26 In addition, our study also showed that the incidence of adverse reactions in the short-term group (4.00%) was lower than that in the long-term group (18.00%), which was similar with the study results of Fan et al 27 and Robinson et al 28 …”
Section: Discussionsupporting
confidence: 91%